Efficacy of canalith repositioning maneuvers in BPPV: A literature review - Ana Beatriz Carreira Favano; Gabriele Andrade Batista; João Pedro Martins Da Silva; Mariana Braz Lourenço; Giovanna Lourenço Pereira; Giovanna Nascimento Ribeiro; Erika Barros Teixeira Da Cruz; Emily Barros Teixeira De Lima; Fabricio Fazolari Di Loreto; Tarik Verissimo de Medeiros Ether; Antonio da Silva Ribeiro; Thayane Soares Ritti; et al. (International Health Sciences Review, 2026)
Benign Paroxysmal Positional Vertigo (BPPV) is the most common peripheral vestibular disorder, characterized by brief episodes of positional vertigo and nystagmus caused by displaced otoconia within the semicircular canals. This narrative literature review synthesizes contemporary clinical, diagnostic, and biomechanical evidence regarding the therapeutic efficacy, procedural safety, and translational outcomes of canalith repositioning maneuvers (CRMs) across BPPV variants. Evidence from randomized controlled trials, clinical practice guidelines, and systematic reviews confirms that canal-specific repositioning procedures—including the Epley, Semont, Semont-plus, Lempert (barbecue roll), and Gufoni maneuvers—provide definitive, rapid mechanical clearance of canaliths, significantly outperforming sham interventions, observation, and Brandt-Daroff habituation exercises (odds ratios > 4.4 to 12.4). Biomechanical in vitro models establish that the Semont maneuver remains effective within head excursion angles of 21^∘ to 67^∘ with minimum waiting times of >30 seconds, while the Semont-plus maneuver accelerates symptom resolution compared to the Epley maneuver (median recovery: 1 vs. 2 days; p=0.01). In acute care settings, a single Epley maneuver provides short-term efficacy and disability reduction comparable to multiple iterations. Routine vestibular suppressants, neuroimaging, and post-procedural postural restrictions are not supported by evidence. Key translational challenges include managing canal switch (occurring in ~4.6% of cases due to cross-canal migration), mitigating multi-year recurrence (36% to 50%), and addressing residual dizziness (affecting 31% to 61% of patients) through patient education and customized vestibular rehabilitation.